Emotional and physical abuse and its relationship to social skills in primary school students - Mahmoud , Anan; Shamel, Shaima (Al-Adab Journal, 2024)
The current research aims to identify emotional and physical abuse and find the indication of differences in abuse among primary school students according to the sex variable (male-female) and identify their social skills and find the indication of differences in social skills according to the sex variable (male-female) and find the relationship between emotional and physical abuse and their social skills, the current research is determined by Primary School students fifth grade of Public Schools in Baghdad within the Directorate of education of the first Rusafa for the academic year (2018-2019) the research sample amounted to (500) the scale of emotional and physical abuse was prepared by (64) paragraphs distributed over Three areas, (29) paragraphs for emotional abuse, (16) paragraphs for physical abuse, and (19) paragraphs for neglect, and the scale of social skills for children was adopted by(Mohammed Sayed Abdul Rahman) the psychometric characteristics of all two scales were extracted, where the coefficient of stability of the scale of abuse reached (0.83) by the retest method and (0.81) by the half-segmentation method and the coefficient of stability of the scale of social skills reached (0.78) by the retest method and (0.77) by the half-segmentation method, and the coefficient of stability of the scale of social skills reached (0.78) by the retest method and (0.77) by the half-segmentation method, and the coefficient of stability of the scale of social skills reached (0.78) by the retest method and (0.77) by the half-segmentation method, the two researchers reached a set of results after analyzing the students ’ data showing an increase in the level of emotional and physical abuse of the sample members and the absence of significant statistical differences between the sample members according to There is a significant decrease in the level of social skills and there are no significant statistical differences between the sample members in social skills with a strong relationship between emotional and physical abuse and social skills among students because abuse leads to the emergence of types of unwanted behaviors such as social withdrawal.